PANDEMI COVID-19 & MAKNA SOSIAL - Bambang Amir Alhakim; Ishomuddin (Discovery, 2022)
Abstract: This study aims to understand the social meaning of some community members for the occurrence of the covid-19 outbreak (pandemic). The method used to reveal the social meaning is descriptive qualitative. In practice, the writers use Max Weber's theory of social action based on "verstehen" and analyzed by Mile, Huberman and Saldana's interactive model to reveal the social meaning of several community members in East Java, Indonesia. The results of this study are as follows: Some community members believe that this covid-19 outbreak (pandemic) is truly seen as a test from God. Some other members of the public think that the COVID-19 outbreak (pandemic) is an engineering or scenario by certain countries to weaken the nations of the world, including Indonesia, for the sake of mere (material) power ambitions. Several other members of the public assumed that this COVID-19 outbreak (pandemic) did exist but had been engineered in such a way that it tends to be exaggerated as a form of terror to the community and tends to blame the government. And, some other community members consider this a disaster and indeed the time has come for the calamity to come during the twin year, 2020 AD. Keywords​: ​​ covid-19 pandemic, social meaning, society, Indonesia